2020
DOI: 10.3389/fmed.2020.00076
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Response to Vedolizumab in Inflammatory Bowel Disease

Abstract: Vedolizumab is known to be safe, well-tolerated, and effective. However, as personalization becomes an increasingly important aspect of IBD care and in lieu of guidelines to inform clinicians on positioning of biologics, there is a need to reliably predict response to inform patient preferences and shared decision-making. Recent data from clinical trials and real-world evidence have elucidated predictors of clinical and endoscopic response while providing the framework to establish predictive models. Current m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…This mode of action does not result in systemic immunosuppression and, consequently, should not increase the risk of cancer or opportunistic infections, including TB. Those findings were confirmed by Ng et al [ 25 ] where TB among study participants was observed rarely and reactivation of HBV and HCV infections was not seen [ 26 ]. Results of the subsequent study by Colombel et al [ 27 ] involving 2,830 patients with nonspecific IBD demonstrated occurrence of TB, sepsis, and Clostridium infections in up to 0.6% patients.…”
Section: Biological Treatment Of Ibdsupporting
confidence: 73%
See 1 more Smart Citation
“…This mode of action does not result in systemic immunosuppression and, consequently, should not increase the risk of cancer or opportunistic infections, including TB. Those findings were confirmed by Ng et al [ 25 ] where TB among study participants was observed rarely and reactivation of HBV and HCV infections was not seen [ 26 ]. Results of the subsequent study by Colombel et al [ 27 ] involving 2,830 patients with nonspecific IBD demonstrated occurrence of TB, sepsis, and Clostridium infections in up to 0.6% patients.…”
Section: Biological Treatment Of Ibdsupporting
confidence: 73%
“…Results of the subsequent study by Colombel et al [ 27 ] involving 2,830 patients with nonspecific IBD demonstrated occurrence of TB, sepsis, and Clostridium infections in up to 0.6% patients. Results from numerous studies indicate that vedolizumab is efficient in inducing and sustaining remission and is considered to be safe and well tolerated [ 23 , 24 , 26 , 28 ]. Studies involving patients with UC suggest that vedolizumab is effective, especially as a second-line treatment after previous therapy with TNF α inhibitors [ 28 , 29 ].…”
Section: Biological Treatment Of Ibdmentioning
confidence: 99%
“…To the contrary, clinical characteristics of patients are easy to collect and may directly help to estimate outcomes. Thus, using clinical parameters for such purposes has been previously suggested [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effectiveness of the drug was confirmed by many real-world observational studies (Chaparro et al, 2018;Christensen et al, 2018;Lenti et al, 2018;Plevris et al, 2019;Scarozza et al, 2020). It was also reported that patients with less severe disease and naïve to tumor necrosis factor (TNF) blockers are more likely to respond to vedolizumab (Dulai et al, 2016;Amiot et al, 2017;Favale et al, 2019;Hupe et al, 2020;Meserve and Dulai, 2020). Overall, the above studies showed also the drug is well-tolerated with an acceptable safety profile (Colombel et al, 2017).…”
Section: Introductionmentioning
confidence: 80%